Perlindungan Hukum bagi Nasabah dalam Penggunaan Data Pribadi oleh Bank untuk Tujuan Komersil Kepada Pihak Ketiga - Kartika Sandi Taurus; Wishnu Dewanto; Anggawira (Syntax Corporation, 2023)
This study aims to obtain information and analyze laws regarding legal protection for customers in the use of personal data by banks for commercial purposes to third parties. Using the approach method in this study is a normative juridical approach. Legal protection for customers as consumers in the banking sector is very important, because in fact the position of the parties between business actors and consumers in this is the bank and customers is often unbalanced. The Bank as a professional financial institution has the obligation to protect customer data, except for tax purposes, settlement of bank receivables submitted to bank receivables affairs submitted to the State Receivables and Auction Affairs Agency/State Receivables Affairs Committee, for judicial purposes in criminal cases, for judicial purposes in civil cases between banks and customers, in the context of exchanging information between banks and upon request, agreement, or power of attorney from the customer made in writing to the party appointed by the customer as stipulated in Article 40 Paragraph (1) concerning Banking 'the bank must keep confidential information about its depository and deposit customers. The essence of legal protection is to protect the interests of depository customers and their deposits stored in a particular bank against a risk of loss.